Effect of single probiotics Lacticaseibacillus casei CGMCC1.5956 and Levilactobacillus brevis CGMCC1.5954 and their combination on the quality of yogurt as fermented milk. (15th June 2022) - Fan, Xiankang; Du, Lihui; Xu, Jue; Shi, Zihang; Zhang, Tao; Jiang, Xiaoxiao; Zeng, Xiaoqun; Wu, Zhen; Pan, Daodong
Abstract: In this study, the effects of single probiotics Lacticaseibacillus casei CGMCC1.5956 ( L. casei 56) and Levilactobacillus brevis CGMCC1.5954 ( L. brevis 54) and their combination on the quality of yogurt as fermented milk were investigated. The main finding was that binary probiotics might promote L. brevis 54 to produce l -glutamic acid and pyruvic acid thereby enhancing probiotic growth and antioxidant capacity. Glycine, serine and threonine metabolism and biosynthesis of amino acids might be considered the main reasons for the binary probiotics promoted the growth of L. brevis 54. A total of 65 volatile flavor substances were identified, including carbonyl compounds, alcohols, aldehydes, and acids. Differences in the metabolic profiles and pathways of volatile and nonvolatile flavor substances between single and binary probiotic bacteria were identified by metabolomics. A mapping of the action of single and binary probiotic flora was provided, which could guide the development of yogurt with unique flavor, high probiotic content, and strong antioxidant capacity. Graphical abstract: Effect of single probiotic L. casei 56 and L. brevis 54 and their combination on yogurt quality. A simplified version of the experimental protocol conducted in this study. Image 1 Highlights: The effects of single and binary probiotics on yogurt quality were compared. Binary probiotics enhanced the antioxidant capacity of yogurt. The Glycine, serine and threonine metabolism could enhance the growth of L. brevis 54. Binary probiotics promoted the production of l -Glutamic acid and Pyruvic acid.